Separation methods
By forming a zeolite membrane complex with small-diameter zeolite crystal grains and a heat treatment process, the method effectively removes organic agents, improving the permeability of zeolite membranes for substances like hydrogen.
Patent Information
- Application Number
- JP2023162892
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-03-26
- Filing Date
- 2023-09-26
- Publication Date
- 2025-01-30
- Estimated Expiration
- 2039-12-10
AI Technical Summary
The removal of organic structure-directing agents from zeolite films with small pore diameters is challenging, particularly for zeolite membranes, which hinders the permeation of substances and reduces their effectiveness.
A method involving the formation of a zeolite membrane complex with a porous support, where zeolite crystal grains with a diameter of 300 nm or less constitute 85% of the surface area, and a heat treatment process to remove organic structure-directing agents, ensuring high permeability for specific substances like hydrogen.
The method enables efficient removal of organic structure-directing agents and enhances the permeability of the zeolite membrane for substances such as hydrogen, achieving a transmission speed of 10 nmol/m²·s·Pa or higher.
Smart Images

Figure 0007624279000001 
Figure 0007624279000002 
Figure 0007624279000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a separation method. By law Regarding. [Background technology]
[0002] Currently, methods for synthesizing zeolites with various structures are known. For example, Patent Document 1 discloses a method for synthesizing an SOD type zeolite powder containing an organic structure-directing agent. The organic structure-directing agent is removed from the zeolite powder by heat treatment. Patent Document 2 discloses a method for synthesizing an SOD type zeolite membrane that does not contain an organic structure-directing agent. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2007-320819 A [Patent Document 2] JP 2012-246207 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, in the case of 6-membered ring zeolites such as SOD type zeolites, the pore size is small, so when an organic structure-directing agent is contained, it is not easy to burn and remove it. In particular, in the case of 6-membered ring zeolite membranes, unlike powders, individual zeolite crystal grains are constrained, so it is more difficult to burn and remove the organic structure-directing agent. In addition, in the case of 6-membered ring zeolite membranes that do not contain an organic structure-directing agent as in Patent Document 2, alkali metals are present in the fine pores of the zeolite, so the permeation amount of the membrane is likely to be low.
[0005] The present invention has been made in consideration of the above problems, and aims to easily remove the organic structure-directing agent from a zeolite membrane made of a six-membered ring zeolite containing the organic structure-directing agent, thereby enabling appropriate separation of highly permeable substances. [Means for solving the problem]
[0006] The present invention is directed to a separation method. A preferred embodiment of the separation method of the present invention includes the steps of: a) preparing a zeolite membrane composite; )a and supplying a mixed gas containing a highly permeable substance selected from ammonia, helium, and hydrogen to the zeolite membrane composite, and separating the highly permeable substance from the mixed gas by permeating the zeolite membrane composite. The zeolite membrane composite comprises a support and a zeolite membrane formed on the support and made of a 6-membered ring zeolite, and among a plurality of zeolite crystal grains located on the surface of the zeolite membrane, zeolite crystal grains having a short axis of 300 nm or less on the surface occupy 85% or more of the area of the surface of the zeolite membrane.
[0007] Preferably, the support is porous.
[0008] Preferably, the He permeation rate of the zeolite membrane composite is 10 nmol / m 2 ·s·Pa or more.
[0009] The present invention Related Technology The zeolite membrane composite according to the present invention comprises a support and a zeolite membrane formed on the support and made of a 6-membered ring zeolite, and has a He permeation rate of 10 nmol / m 2 ·s·Pa or more.
[0010] Preferably, the six-membered ring zeolite is one selected from the group consisting of AFG type, AST type, DOH type, FAR type, FRA type, GIU type, LIO type, LOS type, MAR type, MEP type, MSO type, MTN type, NON type, RUT type, SGT type, SOD type, SVV type, TOL type, and UOZ type.
[0011] Preferably, the six-membered ring zeolite is one selected from the MTN type, the SGT type, and the SOD type.
[0012] Preferably, the zeolite membrane contains Si atoms and Al atoms, and the Si / Al ratio in the zeolite membrane is 5 or more.
[0013] Preferably, the residual rate of the organic SDA in the zeolite membrane is 10% or less. Effect of the Invention
[0014] According to the present invention, the organic structure-directing agent can be easily removed from a zeolite membrane made of a six-membered ring zeolite, and highly permeable substances can be appropriately separated. [Brief description of the drawings]
[0015] [Figure 1] FIG. 2 is a cross-sectional view of a zeolite membrane composite. [Diagram 2] FIG. 2 is an enlarged cross-sectional view showing a part of the zeolite membrane composite. [Diagram 3] FIG. 2 is a diagram showing a flow of production of a zeolite membrane composite. [Figure 4] FIG. [Diagram 5] FIG. 2 is a diagram showing the flow of separation of a mixed material by a separation device. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] FIG. 1 is a cross-sectional view of a zeolite membrane composite 1. FIG. 2 is a cross-sectional view showing an enlarged portion of the zeolite membrane composite 1. The zeolite membrane composite 1 includes a porous support 11 and a zeolite membrane 12 provided on the support 11. The zeolite membrane is at least a membrane of zeolite formed on the surface of the support 11, and does not include a membrane in which zeolite particles are simply dispersed in an organic membrane. In FIG. 1, the zeolite membrane 12 is drawn with a thick line. In FIG. 2, the zeolite membrane 12 is drawn with parallel oblique lines. Also, in FIG. 2, the thickness of the zeolite membrane 12 is drawn thicker than it actually is.
[0017] The support 11 is a porous member that is permeable to gas and liquid. In the example shown in FIG. 1, the support 11 is a monolithic support having a single continuous columnar body that is molded as an integral unit and has a plurality of through holes 111 that extend in the longitudinal direction (i.e., the vertical direction in FIG. 1). In the example shown in FIG. 1, the support 11 is substantially cylindrical. The cross section perpendicular to the longitudinal direction of each through hole 111 (i.e., cell) is, for example, substantially circular. In FIG. 1, the diameter of the through hole 111 is drawn larger than the actual diameter, and the number of the through holes 111 is drawn smaller than the actual number. The zeolite membrane 12 is formed on the inner surface of the through hole 111 and covers the inner surface of the through hole 111 over substantially the entire surface.
[0018] The length of the support 11 (i.e., the length in the vertical direction in FIG. 1) is, for example, 10 cm to 200 cm. The outer diameter of the support 11 is, for example, 0.5 cm to 30 cm. The distance between the central axes of adjacent through holes 111 is, for example, 0.3 mm to 10 mm. The surface roughness (Ra) of the support 11 is, for example, 0.1 μm to 5.0 μm, and preferably 0.2 μm to 2.0 μm. The shape of the support 11 may be, for example, a honeycomb shape, a flat plate shape, a tubular shape, a cylindrical shape, a columnar shape, or a polygonal column shape. When the shape of the support 11 is a tubular or cylindrical shape, the thickness of the support 11 is, for example, 0.1 mm to 10 mm.
[0019] The material of the support 11 may be any of various substances (e.g., ceramics or metals) as long as it has chemical stability in the process of forming the zeolite membrane 12 on the surface. In this embodiment, the support 11 is formed of a ceramic sintered body. Examples of ceramic sintered bodies selected as the material of the support 11 include alumina, silica, mullite, zirconia, titania, yttria, silicon nitride, and silicon carbide. In this embodiment, the support 11 is an alumina sintered body, a mullite sintered body, or a titania sintered body. This improves the adhesion between the zeolite membrane 12 and the support 11.
[0020] The support 11 may contain an inorganic binder, which may be at least one of titania, mullite, sinterable alumina, silica, glass frit, clay minerals, and sinterable cordierite.
[0021] The average pore size of the support 11 is, for example, 0.01 μm to 70 μm, and preferably 0.05 μm to 25 μm. The average pore size of the support 11 in the vicinity of the surface on which the zeolite membrane 12 is formed is 0.01 μm to 1 μm, and preferably 0.05 μm to 0.5 μm. Regarding the distribution of pore sizes throughout the support 11, including the surface and the interior, D5 is, for example, 0.01 μm to 50 μm, D50 is, for example, 0.05 μm to 70 μm, and D95 is, for example, 0.1 μm to 2000 μm. The porosity of the support 11 in the vicinity of the surface on which the zeolite membrane 12 is formed is, for example, 25% to 50%.
[0022] The support 11 has a multilayer structure in which, for example, a plurality of layers having different average pore diameters are laminated in the thickness direction. The average pore diameter and sintered grain size in the surface layer including the surface on which the zeolite membrane 12 is formed are smaller than the average pore diameter and sintered grain size in the layers other than the surface layer. The average pore diameter of the surface layer of the support 11 is, for example, 0.01 μm to 1 μm, and preferably 0.05 μm to 0.5 μm. When the support 11 has a multilayer structure, the materials for each layer can be those described above. The materials for the layers forming the multilayer structure may be the same or different.
[0023] The zeolite membrane 12 is a porous membrane having fine pores (micropores). The zeolite membrane 12 can be used as a separation membrane that separates a specific substance from a mixture of a plurality of types of substances by utilizing a molecular sieve effect. Other substances are less likely to permeate the zeolite membrane 12 than the specific substance. In other words, the amount of the other substances that permeates the zeolite membrane 12 is smaller than the amount of the specific substance that permeates the zeolite membrane 12. As described later, the fine pores in the zeolite membrane 12 are very small, and substances that permeate a large amount are, for example, water (H2O), ammonia (NH3), helium (He), hydrogen (H2), and the like.
[0024] The thickness of the zeolite membrane 12 is, for example, 0.05 μm to 30 μm, preferably 0.1 μm to 20 μm, and more preferably 0.5 μm to 10 μm. When the zeolite membrane 12 is made thicker, the separation performance is improved. When the zeolite membrane 12 is made thinner, the permeation rate is increased. The surface roughness (Ra) of the zeolite membrane 12 is, for example, 5 μm or less, preferably 2 μm or less, more preferably 1 μm or less, and more preferably 0.5 μm or less.
[0025] The maximum number of rings in the zeolite constituting the zeolite membrane 12 is 6. That is, the zeolite membrane 12 is a 6-membered ring zeolite membrane made of 6-membered ring zeolite whose maximum number of rings is 6. The zeolite membrane 12 is typically made of only 6-membered ring zeolite, but depending on the production method, etc., the zeolite membrane 12 may contain a small amount (for example, 1 mass % or less) of a substance other than the 6-membered ring zeolite.
[0026] In this embodiment, the average pore size of the zeolite is the arithmetic average of the short diameter and the long diameter of the six-membered ring pores. The six-membered ring pores are micropores in which the number of oxygen atoms in the portion in which the oxygen atoms are bonded to the T atom described below to form a ring structure is six. When the zeolite has a plurality of six-membered ring pores, the average pore size of the zeolite is the arithmetic average of the short diameter and the long diameter of all the six-membered ring pores. In this way, the average pore size of the zeolite membrane is uniquely determined by the framework structure of the zeolite.
[0027] The average pore diameter of the zeolite membrane 12 is, for example, 0.3 nm or less. The average pore diameter of the zeolite membrane 12 is preferably 0.2 nm or more and 0.3 nm or less. The average pore diameter of the zeolite membrane 12 is smaller than the average pore diameter of the support 11 in the vicinity of the surface on which the zeolite membrane 12 is formed.
[0028] The type of zeolite constituting the zeolite membrane 12 is not particularly limited as long as it is a 6-membered ring zeolite, and may be, for example, AFG type, AST type, DOH type, FAR type, FRA type, GIU type, LIO type, LOS type, MAR type, MEP type, MSO type, MTN type, NON type, RUT type, SGT type, SOD type, SVV type, TOL type, UOZ type, etc.
[0029] The zeolite membrane 12 contains, for example, silicon (Si). The zeolite membrane 12 may contain, for example, any two or more of Si, aluminum (Al) and phosphorus (P). In this case, the zeolite constituting the zeolite membrane 12 may be a zeolite in which the atom (T atom) located at the center of the oxygen tetrahedron (TO4) constituting the zeolite is only Si or is composed of Si and Al, an AlPO type zeolite in which the T atom is composed of Al and P, a SAPO type zeolite in which the T atom is composed of Si, Al and P, a MAPSO type zeolite in which the T atom is composed of magnesium (Mg), Si, Al and P, or a ZnAPSO type zeolite in which the T atom is composed of zinc (Zn), Si, Al and P. Some of the T atoms may be substituted with other elements.
[0030] When the zeolite membrane 12 contains Si atoms and Al atoms, the Si / Al ratio in the zeolite membrane 12 is, for example, 1 or more and 100,000 or less. The Si / Al ratio is preferably 5 or more, more preferably 20 or more, and even more preferably 100 or more, and the higher the ratio, the better. The Si / Al ratio in the zeolite membrane 12 can be adjusted by adjusting the mixing ratio of the Si source and the Al source in the raw material solution, which will be described later. The zeolite membrane 12 may contain an alkali metal. The alkali metal is, for example, sodium (Na) or potassium (K).
[0031] The zeolite membrane 12 may contain a small amount of an organic structure-directing agent (hereinafter also referred to as "organic SDA"). That is, the zeolite constituting the zeolite membrane 12 may contain an organic SDA. The organic SDA is used in the formation of the zeolite membrane 12. As described later, a preferred zeolite membrane 12 contains almost no organic SDA.
[0032] The zeolite membrane 12 is a polycrystalline membrane mainly composed of a large number of zeolite crystal grains formed on the surface of the support 11. In an electron microscope image (e.g., an image at 30,000 times magnification) obtained by observing the surface of the zeolite membrane 12 with a scanning electron microscope (SEM) from a direction approximately perpendicular to the surface, a state in which a plurality of zeolite crystal grains are densely packed is confirmed. Here, in the electron microscope image, when two parallel lines that contact the outer edge of each zeolite crystal grain and sandwich the zeolite crystal grain are set in various directions, the width between the two parallel lines at the minimum is defined as the "minor axis". In the zeolite membrane 12, the proportion of the area of zeolite crystal grains having a minor axis of 300 nm or less in the surface area (projected area) of the zeolite membrane 12 in the electron microscope image is 85% or more. The proportion of the area is preferably 90% or more, more preferably 95% or more. In the zeolite membrane 12, a large number of zeolite crystal grains each having a small minor axis are densely packed together, so that the grain boundaries and surface area on the surface of the zeolite membrane 12 are large.
[0033] Next, referring to FIG. 3, an example of a flow of manufacturing the zeolite membrane composite 1 will be described. When the zeolite membrane composite 1 is manufactured, first, seed crystals to be used for forming the zeolite membrane 12 are generated and prepared (step S11). In generating the seed crystals, for example, a Si source, a P source, an Al source, an organic SDA, and the like are dissolved or dispersed in a solvent to prepare a raw material solution. For example, water or an alcohol such as ethanol can be used as the solvent for the raw material solution. For example, colloidal silica, fumed silica, silicon alkoxide, sodium silicate, and the like can be used as the Si source. For example, phosphoric acid, diphosphorus pentoxide, sodium dihydrogen phosphate, ammonium dihydrogen phosphate, phosphate ester, and the like can be used as the P source. For example, sodium aluminate, aluminum hydroxide, aluminum alkoxide, alumina sol, and the like can be used as the Al source. For example, amines, quaternary ammonium salts, and the like can be used as the organic SDA. The raw material solution does not necessarily need to contain all of the Si source, the P source, and the Al source. In another example, the raw material solution contains a Si source. In still another example, the raw material solution contains any two of a Si source, a P source, and an Al source. The same applies to the raw material solution in step S13 described later.
[0034] Next, the raw material solution is subjected to hydrothermal synthesis. The temperature during the hydrothermal synthesis is, for example, 110 to 200°C. The hydrothermal synthesis time is, for example, 5 to 100 hours. When the hydrothermal synthesis is completed, the obtained crystals are washed with pure water. Then, the washed crystals are dried to produce a powder of 6-membered ring zeolite. The 6-membered ring zeolite is, for example, SOD type zeolite or SGT type zeolite. The composition of the 6-membered ring zeolite can be adjusted by adjusting the blending ratio of the raw materials (Si source, P source, Al source, etc.) in the raw material solution.
[0035] Although the powder of the six-membered ring zeolite can be used as the seed crystals as it is, it is preferable to process the powder by pulverization or the like to obtain seed crystals whose particle size is adjusted to match the pore size of the surface layer of the support 11 (for example, seed crystals whose average particle size is larger than the average pore size of the surface layer of the support 11). The powder of the six-membered ring zeolite may be prepared by other methods.
[0036] Next, the porous support 11 is immersed in the dispersion liquid in which the seed crystals are dispersed, and the seed crystals are adhered to the support 11 (step S12). Alternatively, the dispersion liquid in which the seed crystals are dispersed is brought into contact with a portion of the support 11 on which the zeolite membrane 12 is to be formed, thereby adhering the seed crystals to the support 11. In this manner, a seed crystal-adhered support is produced. At this time, for example, the concentration of the seed crystals in the dispersion liquid and the like are adjusted so that the mass of seed crystals adhered per unit area (hereinafter referred to as "adhesion density") in the portion of the support 11 on which the zeolite membrane 12 is to be formed is a predetermined value or more. The adhesion density in this embodiment is, for example, 0.1 g / m 2 or more, preferably 0.15 g / m 2 More preferably, it is 0.2 g / m or more. 2 The adhesion density is, for example, 2.0 g / m 2 The seed crystal may also be attached to the support 11 by other techniques.
[0037] The support 11 to which the seed crystals are attached is immersed in the raw material solution. The raw material solution is prepared by dissolving or dispersing, for example, a Si source, a P source, an Al source, an organic SDA, and the like in a solvent, in the same manner as the raw material solution in step S11 (at the time of generating the seed crystals). Specific examples of the Si source, the P source, the Al source, the organic SDA, and the solvent are the same as those in the raw material solution in step S11. As described above, the raw material solution does not necessarily contain all of the Si source, the P source, and the Al source. Thereafter, the zeolite is grown by hydrothermal synthesis using the seed crystals on the support 11 as nuclei, thereby forming a zeolite membrane 12 made of a 6-membered ring zeolite on the support 11 (step S13). The temperature during the hydrothermal synthesis is, for example, 110 to 200° C. The hydrothermal synthesis time is, for example, 5 to 100 hours.
[0038] As described above, the seed crystals are attached to the surface of the support 11 at a high attachment density (densely). In step S13, appropriate synthesis conditions are selected according to the type of zeolite to be formed, and zeolite crystal grains grow in the film thickness direction with the seed crystals as nuclei. As a result, the zeolite membrane 12 is formed in which a large number of zeolite crystal grains are densely packed and spread out. When the zeolite membrane 12 is viewed from its normal direction (film thickness direction), among the multiple zeolite crystal grains located on the surface of the zeolite membrane 12, zeolite crystal grains having a short diameter of 300 nm or less on the surface occupy 85% or more of the area (projected area) of the surface. Typically, most of the multiple zeolite crystal grains located on the surface of the zeolite membrane 12 are single crystal grains that are continuous in the normal direction of the surface of the support 11, except for the seed crystals. Note that, as long as the zeolite membrane 12 made of 6-membered ring zeolite can be formed, the type of raw material contained in the raw material solution in step S13 may be different from the type of raw material contained in the raw material solution in step S11.
[0039] When the hydrothermal synthesis is completed, the support 11 and the zeolite membrane 12 are washed with pure water. The washed support 11 and the zeolite membrane 12 are dried, for example, at 100°C. After the support 11 and the zeolite membrane 12 are dried, the zeolite membrane 12 is heat-treated in an oxidizing gas atmosphere, whereby the organic SDA in the zeolite membrane 12 is burned and removed by being desorbed from the grain boundaries and crystal surfaces (step S14). This penetrates the micropores in the zeolite membrane 12. Preferably, most of the organic SDA in the zeolite membrane 12 is removed. The heating temperature for removing the organic SDA is, for example, 400 to 1000°C, preferably 400 to 900°C, and more preferably 450 to 800°C. If the heating temperature is higher than 1000°C, the separation performance of the zeolite membrane 12 may be reduced. If the heating temperature is lower than 400°C, the organic SDA in the zeolite membrane 12 may not be sufficiently removed. The heating time is, for example, 10 to 200 hours. The oxidizing gas atmosphere is an atmosphere containing oxygen, for example, air. By the above-mentioned treatment, the zeolite membrane composite 1 is obtained.
[0040] For example, the amount of mass reduction when the zeolite membrane composite 1 is heated to a temperature higher than 1000° C. to decompose the organic SDA can be regarded as the amount of organic SDA remaining in the zeolite membrane 12 of the zeolite membrane composite 1. The amount of organic SDA removed by the heat treatment can be calculated from the change in mass before and after the heat treatment in step S14. The proportion of the remaining amount of organic SDA in the sum of the amount of organic SDA removed by the heat treatment and the remaining amount of organic SDA is the remaining ratio of organic SDA in the zeolite membrane 12 of the zeolite membrane composite 1, and the remaining ratio is, for example, 10% or less, preferably 5% or less. The ratio of the remaining amount of organic SDA to the mass of the zeolite membrane 12 is, for example, 3% or less, preferably 1% or less.
[0041] In the manufacture of the above-mentioned zeolite membrane composite 1, the support 11 is immersed in a raw material solution containing the organic SDA, and the zeolite membrane 12 made of 6-membered ring zeolite is formed on the support 11 by hydrothermal synthesis. The organic SDA is then removed from the zeolite membrane 12 by heat treatment. At this time, among the multiple zeolite crystal grains located on the surface of the zeolite membrane 12, zeolite crystal grains having a short diameter of 300 nm or less on the surface occupy 85% or more of the area of the surface of the zeolite membrane 12. In the above-mentioned heat treatment, in order for the organic SDA combusted and decomposed in the zeolite membrane 12 to be desorbed from the zeolite membrane 12, the combusted and decomposed organic SDA needs to diffuse to the grain boundary or the crystal surface. On the other hand, in the 6-membered ring zeolite with a small pore size, the diffusion speed of the combusted and decomposed organic SDA is slow, so that the organic SDA may not be sufficiently removed by the heat treatment. However, if the short diameter of the 6-membered ring zeolite crystal grains in the zeolite membrane 12 is 300 nm or less, the organic SDA combusted and decomposed can diffuse to nearby grain boundaries in a relatively short time even at the heat treatment temperature (e.g., 400 to 1000°C) and can quickly reach and be removed through the grain boundaries to the surface of the zeolite membrane 12. In this way, by packing zeolite crystal grains with a small short diameter closely together, the organic SDA can be easily removed from the zeolite membrane 12 during heat treatment.
[0042] Moreover, by attaching seed crystals onto the support 11 before forming the zeolite membrane 12, the zeolite membrane 12 having densely packed zeolite crystal grains with small short diameters can be easily formed. Furthermore, by heating the zeolite membrane 12 at a temperature of 400 to 1000°C in the heat treatment, it becomes possible to more reliably remove the structured SDA from the zeolite membrane 12. In other words, if the zeolite membrane 12 has zeolite crystal grains with short diameters of 300 nm or less among the multiple zeolite crystal grains located on the surface, occupying 85% or more of the surface area, the structured SDA can be reliably removed from the zeolite membrane 12 even by heat treatment at 400 to 1000°C.
[0043] The He gas permeation rate (He permeation rate) of the zeolite membrane 12 is 10 nmol / m 2 s Pa or more, and 20 nmol / m 2 s Pa or more, and 30 nmol / m 2 It is particularly preferable that the He gas permeability test of the zeolite membrane 12 is performed with the pressure (gauge pressure) of the introduced He gas set to 0.5 MPaG and the pressure (gauge pressure) of the permeated He gas set to 0 MPaG. 2 By setting the pressure at .s.Pa or more, the organic SDA can be sufficiently removed, and the zeolite membrane 12 having high permeability can be obtained.
[0044] Next, an example of the production of the zeolite membrane composite 1 will be described.
[0045] <Example 1> First, colloidal silica, phosphoric acid, aluminum hydroxide, and tetramethylammonium hydroxide, which is an organic SDA (organic structure directing agent), were dissolved in pure water to prepare a raw material solution with a composition of 1SiO2:1P2O5:0.2Al2O3:2SDA:400H2O. The raw material solution was subjected to hydrothermal synthesis at 170°C for 20 hours to obtain SOD type zeolite powder.
[0046] SOD type zeolite powder was added to pure water so as to have a concentration of 7 to 8 mass %, and pulverized in a ball mill to prepare a dispersion liquid of SOD type zeolite seed crystals.
[0047] A monolithic support was immersed in a dispersion of SOD type zeolite seed crystals, and the SOD type zeolite seed crystals were dispersed at a concentration of 0.1 g / m 2 The adhesive was applied to the inner surface of each through hole of the support in the above manner.
[0048] Next, colloidal silica, phosphoric acid, aluminum hydroxide, and tetramethylammonium hydroxide, which is an organic SDA, were dissolved in pure water to prepare a raw material solution with the composition 1SiO2:1P2O5:0.2Al2O3:2SDA:4000H2O.
[0049] Next, the support with the seed crystals attached was immersed in the raw material solution and hydrothermally synthesized at 150°C for 20 hours. As a result, an SOD-type zeolite membrane was formed on the support. After hydrothermal synthesis, the support and the zeolite membrane were thoroughly washed with pure water and then dried at 100°C. When the surface of the zeolite membrane was observed with a scanning electron microscope (SEM), zeolite crystal grains with a short diameter of 300 nm or less accounted for 85% or more of the area of the zeolite membrane surface.
[0050] After drying the support and the zeolite membrane, the N2 (nitrogen) gas permeation rate of the zeolite membrane was measured. As described above, the zeolite membrane is formed on the inner surface of a plurality of through holes of the support. Both ends of the support are sealed with glass, and the support is housed in an outer cylinder (see FIG. 4 described later). That is, the zeolite membrane composite is placed in the outer cylinder. Furthermore, a seal member is placed between both ends of the support and the outer cylinder. In this state, N2 gas is introduced into each through hole of the support, and N2 gas that has permeated the zeolite membrane is collected from a hole provided in the outer cylinder. The pressure (gauge pressure) of the introduced N2 gas was 0.3 MPaG, and the pressure (gauge pressure) of the permeated N2 gas was 0 MPaG. As a result, the N2 permeation rate of the zeolite membrane was 0.005 nmol / m 2The pressure drop was less than 1.0 s Pa. This confirmed that the zeolite membrane had a density sufficient for practical use. The zeolite membrane was then heat-treated at 700°C for 50 hours.
[0051] Next, the He gas permeation rate was measured. The He gas permeation test was carried out in the same manner as the N2 gas permeation test described above. In the permeation test, the pressure (gauge pressure) of the introduced He gas was set to 0.5 MPaG, and the pressure (gauge pressure) of the permeated He gas was set to 0 MPaG, and it was confirmed that He gas permeated the zeolite membrane. The He permeation rate was 10 nmol / m 2 s Pa or more. This confirmed that the organic SDA in the zeolite membrane was sufficiently removed by heating.
[0052] <Example 2> First, colloidal silica, sodium hydroxide, and 1-adamantanamine, an organic SDA (organic structure directing agent), were dissolved in pure water to prepare a raw material solution with a composition of 20SiO2:1Na2O:7SDA:800H2O. The raw material solution was subjected to hydrothermal synthesis at 180°C for 100 hours to obtain SGT-type zeolite powder.
[0053] SGT zeolite powder was added to pure water so as to have a concentration of 7 to 8 mass %, and pulverized in a ball mill to prepare a dispersion of SGT zeolite seed crystals.
[0054] A monolithic support was immersed in a dispersion of SGT zeolite seed crystals, and the SGT zeolite seed crystals were dispersed at a concentration of 0.1 g / m 2 The adhesive was applied to the inner surface of each through hole of the support in the above manner.
[0055] Next, colloidal silica and 1-adamantanamine, an organic SDA, were dissolved in pure water to prepare a raw material solution with a composition of 50SiO2:1SDA:1000H2O.
[0056] Next, the support with the seed crystals attached was immersed in the raw material solution and hydrothermally synthesized at 160°C for 20 hours. As a result, an SGT type zeolite membrane was formed on the support. After hydrothermal synthesis, the support and the zeolite membrane were thoroughly washed with pure water and then dried at 100°C. When the surface of the zeolite membrane was observed with an SEM, zeolite crystal grains with a short diameter of 300 nm or less accounted for 85% or more of the area of the zeolite membrane surface.
[0057] After drying the support and the zeolite membrane, the N2 gas permeation rate of the zeolite membrane was measured. The N2 gas permeation rate of the zeolite membrane was 0.005 nmol / m 2 The pressure drop was less than 1.0 s Pa. This confirmed that the zeolite membrane had a density sufficient for practical use. The zeolite membrane was then heat-treated at 700°C for 50 hours.
[0058] Next, a He gas permeation test was carried out in the same manner as in Example 1. As a result, it was confirmed that He gas permeated the zeolite membrane. The He permeation rate was 10 nmol / m 2 s Pa or more. This confirmed that the organic SDA in the zeolite membrane was sufficiently removed by heating.
[0059] <Example 3> First, colloidal silica and tetramethylammonium hydroxide, an organic SDA (organic structure directing agent), were dissolved in pure water to prepare a raw material solution with a composition of 1SiO2:0.5SDA:200H2O. The raw material solution was subjected to hydrothermal synthesis at 180°C for 50 hours to obtain MTN-type zeolite powder.
[0060] MTN type zeolite powder was added to pure water so as to have a concentration of 7 to 8 mass %, and pulverized in a ball mill to prepare a dispersion liquid of MTN type zeolite seed crystals.
[0061] A monolithic support was immersed in a dispersion of MTN type zeolite seed crystals, and the MTN type zeolite seed crystals were dispersed in the dispersion at a concentration of 0.1 g / m 2 The adhesive was applied to the inner surface of each through hole of the support in the above manner.
[0062] Next, colloidal silica and tetramethylammonium hydroxide, which is an organic SDA, were dissolved in pure water to prepare a raw material solution with a composition of 1SiO2:0.3SDA:1000H2O.
[0063] Next, the support with the seed crystals attached was immersed in the raw material solution and hydrothermally synthesized at 170°C for 10 hours. As a result, an MTN-type zeolite membrane was formed on the support. After hydrothermal synthesis, the support and the zeolite membrane were thoroughly washed with pure water and then dried at 100°C. When the surface of the zeolite membrane was observed with an SEM, zeolite crystal grains with a short diameter of 300 nm or less accounted for 85% or more of the area of the zeolite membrane surface.
[0064] After drying the support and the zeolite membrane, the N2 gas permeation rate of the zeolite membrane was measured. The N2 gas permeation rate of the zeolite membrane was 0.005 nmol / m 2 The pressure drop was less than 1.0 s Pa. This confirmed that the zeolite membrane had a density sufficient for practical use. The zeolite membrane was then heat-treated at 700°C for 50 hours.
[0065] Next, a He gas permeation test was carried out in the same manner as in Example 1. As a result, it was confirmed that He gas permeated the zeolite membrane. The He permeation rate was 10 nmol / m 2 s Pa or more. This confirmed that the organic SDA in the zeolite membrane was sufficiently removed by heating.
[0066] <Comparative Example 1> SOD type zeolite seed crystals at 0.1 g / m 2 A zeolite membrane was produced in the same manner as in Example 1, except that the zeolite crystal grains were attached to the inner surface of each through-hole of the support so that the thickness of the zeolite crystal grains was less than 100 nm. When the surface of the zeolite membrane was observed by SEM, zeolite crystal grains having a minor axis of 300 nm or less accounted for 50% or less of the area of the zeolite membrane surface.
[0067] After drying the support and the zeolite membrane, the N2 gas permeation rate of the zeolite membrane was measured. The N2 gas permeation rate of the zeolite membrane was 0.005 nmol / m 2 The pressure drop was less than 1.0 s Pa. This confirmed that the zeolite membrane had a density sufficient for practical use. The zeolite membrane was then heat-treated at 700°C for 50 hours.
[0068] Next, a He gas permeation test was carried out in the same manner as in Example 1. As a result, He gas hardly permeated the zeolite membrane, which confirmed that the organic SDA in the zeolite membrane was not sufficiently burned off.
[0069] <Comparative Example 2> SGT zeolite seed crystals at 0.1 g / m 2 A zeolite membrane was produced in the same manner as in Example 2, except that the zeolite crystal grains were attached to the inner surface of each through-hole of the support so that the thickness of the zeolite crystal grains was less than 100 nm. When the surface of the zeolite membrane was observed by SEM, zeolite crystal grains having a minor axis of 300 nm or less accounted for 50% or less of the area of the zeolite membrane surface.
[0070] After drying the support and the zeolite membrane, the N2 gas permeation rate of the zeolite membrane was measured. The N2 gas permeation rate of the zeolite membrane was 0.005 nmol / m 2 The pressure drop was less than 1.0 s Pa. This confirmed that the zeolite membrane had a density sufficient for practical use. The zeolite membrane was then heat-treated at 700°C for 50 hours.
[0071] Next, a He gas permeation test was carried out in the same manner as in Example 1. As a result, He gas hardly permeated the zeolite membrane, which confirmed that the organic SDA in the zeolite membrane was not sufficiently burned off.
[0072] Next, separation of a mixed substance using the zeolite membrane composite 1 will be described with reference to Fig. 4 and Fig. 5. Fig. 4 is a diagram showing a separation device 2. Fig. 5 is a diagram showing a flow of separation of a mixed substance by the separation device 2.
[0073] In the separation device 2, a mixed substance containing a plurality of types of fluids (i.e., gas or liquid) is supplied to the zeolite membrane composite 1, and a highly permeable substance in the mixed substance is separated from the mixed substance by permeating the zeolite membrane composite 1. Separation in the separation device 2 may be performed, for example, for the purpose of extracting a highly permeable substance from the mixed substance, or for the purpose of concentrating a less permeable substance. As described above, examples of highly permeable substances in the zeolite membrane composite 1 include water (H2O), ammonia (NH3), helium (He), and hydrogen (H2). There is no particular limitation on the less permeable substance.
[0074] The mixed substance (i.e., mixed fluid) may be a mixed gas containing multiple types of gases, a mixed liquid containing multiple types of liquids, or a gas-liquid two-phase fluid containing both gas and liquid.
[0075] In the following description, it is assumed that the mixed substance separated by the separation device 2 is a mixed gas containing a plurality of types of gases.
[0076] The separation device 2 includes a zeolite membrane composite 1, a plugging section 21, an outer cylinder 22, two seal members 23, a supply section 26, a first recovery section 27, and a second recovery section 28. The zeolite membrane composite 1, the plugging section 21, and the seal members 23 are housed in the outer cylinder 22. The supply section 26, the first recovery section 27, and the second recovery section 28 are disposed outside the outer cylinder 22 and connected to the outer cylinder 22.
[0077] The sealing portion 21 is a member attached to both ends of the support 11 in the longitudinal direction (i.e., the left-right direction in FIG. 4) and covers and seals both longitudinal end faces of the support 11 and the outer side faces near the both end faces. The sealing portion 21 prevents the inflow and outflow of gas from the both end faces of the support 11. The sealing portion 21 is, for example, a plate-like member formed of glass or resin. The material and shape of the sealing portion 21 may be changed as appropriate. Note that the sealing portion 21 has a plurality of openings that overlap with the plurality of through holes 111 of the support 11, and therefore both longitudinal ends of each through hole 111 of the support 11 are not covered by the sealing portion 21. Therefore, gas and the like can flow in and out of the through holes 111 from both ends.
[0078] The shape of the outer cylinder 22 is not limited, and is, for example, a substantially cylindrical tubular member. The outer cylinder 22 is formed of, for example, stainless steel or carbon steel. The longitudinal direction of the outer cylinder 22 is substantially parallel to the longitudinal direction of the zeolite membrane composite 1. A supply port 221 is provided at one end of the outer cylinder 22 in the longitudinal direction (i.e., the end on the left side in FIG. 4), and a first discharge port 222 is provided at the other end. A second discharge port 223 is provided on the side of the outer cylinder 22. A supply unit 26 is connected to the supply port 221. A first recovery unit 27 is connected to the first discharge port 222. A second recovery unit 28 is connected to the second discharge port 223. The internal space of the outer cylinder 22 is a sealed space isolated from the space around the outer cylinder 22.
[0079] The two seal members 23 are disposed around the entire circumference between the outer surface of the zeolite membrane composite 1 and the inner surface of the outer tube 22 near both longitudinal ends of the zeolite membrane composite 1. Each seal member 23 is a substantially annular member made of a material that is gas impermeable. The seal member 23 is, for example, an O-ring made of a flexible resin. The seal member 23 is in close contact with the outer surface of the zeolite membrane composite 1 and the inner surface of the outer tube 22 around the entire circumference. In the example shown in FIG. 4, the seal member 23 is in close contact with the outer surface of the sealing portion 21 and indirectly in close contact with the outer surface of the zeolite membrane composite 1 via the sealing portion 21. The gap between the seal member 23 and the outer surface of the zeolite membrane composite 1 and the gap between the seal member 23 and the inner surface of the outer tube 22 are sealed, and gas is hardly or completely prevented from passing through.
[0080] The supply unit 26 supplies the mixed gas to the internal space of the outer cylinder 22 via the supply port 221. The supply unit 26 is, for example, a blower or a pump that pressure-feeds the mixed gas toward the outer cylinder 22. The blower or pump includes a pressure adjustment unit that adjusts the pressure of the mixed gas supplied to the outer cylinder 22. The first recovery unit 27 and the second recovery unit 28 are, for example, a storage container that stores the gas derived from the outer cylinder 22, or a blower or a pump that transfers the gas.
[0081] When the mixed gas is separated, the above-mentioned separation device 2 is prepared, and thereby the zeolite membrane composite 1 is prepared (step S21). Then, the supply unit 26 supplies the mixed gas containing a plurality of types of gases having different permeabilities to the zeolite membrane 12 to the internal space of the outer casing 22. The pressure of the mixed gas supplied from the supply unit 26 to the internal space of the outer casing 22 (i.e., the introduction pressure) is, for example, 0.1 MPa to 20.0 MPa. The temperature at which the mixed gas is separated is, for example, 10°C to 150°C.
[0082] The mixed gas supplied from the supply unit 26 to the outer cylinder 22 is introduced into each through hole 111 of the support 11 from the left end of the zeolite membrane composite 1 in the figure, as shown by the arrow 251. A gas having high permeability in the mixed gas (hereinafter referred to as a "high permeability substance") permeates the zeolite membrane 12 provided on the inner surface of each through hole 111 and the support 11, and is discharged from the outer surface of the support 11. As a result, the high permeability substance is separated from a gas having low permeability in the mixed gas (hereinafter referred to as a "low permeability substance") (step S22). The gas discharged from the outer surface of the support 11 (hereinafter referred to as a "permeation substance") is recovered by the second recovery unit 28 through the second discharge port 223, as shown by the arrow 253. The pressure of the gas recovered by the second recovery unit 28 through the second discharge port 223 (i.e., the permeation pressure) is, for example, about 1 atmosphere (0.101 MPa).
[0083] In addition, gases other than the gas that has permeated the zeolite membrane 12 and the support 11 (hereinafter referred to as "non-permeating substances") in the mixed gas pass through each through hole 111 of the support 11 from the left side to the right side in the figure, and are collected by the first recovery section 27 through the first discharge port 222 as shown by the arrow 252. The pressure of the gas collected by the first recovery section 27 through the first discharge port 222 is, for example, approximately the same as the introduction pressure. The non-permeating substances may include highly permeable substances that did not permeate the zeolite membrane 12, in addition to the above-mentioned low-permeable substances. In the separation device 2 of FIG. 4, the highly permeable substances can be appropriately separated using the zeolite membrane 12 of a 6-membered ring zeolite from which the organic SDA has been removed.
[0084] The zeolite membrane composite 1 and its production can be modified in various ways.
[0085] In the production of the zeolite membrane composite 1 in Fig. 3, it is also possible to omit the steps of attaching seed crystals to the support 11 (steps S11 and S12 in Fig. 3) and directly form the zeolite membrane 12 on the support 11 in the treatment of step S13. On the other hand, in order to easily form the zeolite membrane 12 having dense zeolite crystal grains with a small minor axis, it is preferable to attach seed crystals to the support 11 before forming the zeolite membrane 12.
[0086] The zeolite membrane composite 1 may further include a functional membrane or a protective membrane laminated on the zeolite membrane 12, in addition to the support 11 and the zeolite membrane 12. Such a functional membrane or protective membrane may be an inorganic membrane such as a zeolite membrane, a silica membrane, or a carbon membrane, or an organic membrane such as a polyimide membrane or a silicone membrane. In addition, a substance that easily adsorbs specific molecules may be added to the functional membrane or protective membrane laminated on the zeolite membrane 12.
[0087] In the above embodiment, the support 11 is porous, so that the zeolite membrane composite 1 suitable for the separation device 2 can be obtained. However, depending on the design of the zeolite membrane composite 1, the support 11 may be non-porous, i.e., a material having almost no pores.
[0088] The configurations in the above-described embodiment and each of the modified examples may be combined as appropriate as long as they are not mutually inconsistent. [Industrial Applicability]
[0089] the above The zeolite membrane composite can be used, for example, as a gas separation membrane, and further, can be used in various fields in which zeolites are used, such as separation membranes for substances other than gases and adsorption membranes for various substances. [Explanation of symbols]
[0090] 1 Zeolite membrane composite 11 Support 12 Zeolite membrane S11~S14, S21, S22 steps
Claims
1. A method of separation comprising the steps of: a) providing a zeolite membrane composite; b) supplying a mixed gas containing a highly permeable substance selected from ammonia, helium, and hydrogen to the zeolite membrane composite, and separating the highly permeable substance from the mixed gas by permeating the highly permeable substance through the zeolite membrane composite; Equipped with The zeolite membrane composite is A support; a zeolite membrane formed on the support and made of a 6-membered ring zeolite; Equipped with A separation method characterized in that, among the multiple zeolite crystal grains located on the surface of the zeolite membrane, zeolite crystal grains having a short diameter of 300 nm or less on the surface occupy 85% or more of the area of the surface of the zeolite membrane.
2. 2. The method of claim 1 , further comprising the steps of: A method for separation, characterized in that the support is porous.
3. The method for separation according to claim 1 or 2, The He permeation rate of the zeolite membrane composite is 10 nmol / m 2 .s·Pa or more.
Citation Information
Patent Citations
Highly pure aluminophosphate zeolite, its production method and its application
JP2007320819A
Hydrogen separation method and hydrogen separation device
JP2012246207A